Economic burden of periodontitis in the United States and Europe – an updated estimation (2021)
Background The aim of this study is to estimate the direct and indirect economic burdens of periodontal disease in the US and in Europe. Methods We used the most recent data available for the US and for Europe (32 European countries) to estimate the cost of periodontal disease. Global health, dental and periodontal expenditures were estimated. We tried to estimate the direct and the indirect costs of periodontitis. Indirect costs, those related to productivity losses, are a consequence of periodontal disease proper, plus edentulism and caries because of periodontal disease. Results In 2018, the aggregate cost in the US was estimated at $3.49B and €2.52B in Europe. Indirect costs because of periodontal disease amounted to $150.57B (95% confidence interval [CI]: 103.32-189.87) in the US countries and €156.12B (95% CI: 123.72-221.86) in Europe. The majority of the projected indirect costs were because of edentulism related to periodontal disease and periodontal disease. Indirect costs were the majority of the estimated economic impact with an average of 0.73% (95% CI: 0.50%-0.93%) of annual gross domestic product in the US and 0.99% (95% CI: 0.78%-1.40%) in Europe. Conclusions Periodontal disease caused an estimated loss of $154.06B in the US and €158.64B in Europe, in 2018. These results show that the economic burden of periodontal disease is significant and its indirect costs are impactful.